Extracellular Vesicles for the Treatment of Radiation Injuries - Nanduri, Lalitha Sarad Yamini; Duddempudi, Phaneendra K.; Yang, Weng-Lang; Tamarat, Radia; Guha, Chandan (Frontiers in Pharmacology, 2021)
Normal tissue injury from accidental or therapeutic exposure to high-dose radiation can cause severe acute and delayed toxicities, which result in mortality and chronic morbidity. Exposure to single high-dose radiation leads to a multi-organ failure, known as acute radiation syndrome, which is caused by radiation-induced oxidative stress and DNA damage to tissue stem cells. The radiation exposure results in acute cell loss, cell cycle arrest, senescence, and early damage to bone marrow and intestine with high mortality from sepsis. There is an urgent need for developing medical countermeasures against radiation injury for normal tissue toxicity. In this review, we discuss the potential of applying secretory extracellular vesicles derived from mesenchymal stromal/stem cells, endothelial cells, and macrophages for promoting repair and regeneration of organs after radiation injury.